A Note on Asymptotic Equilibrium for Fuzzy Differential Equations - Yabin Shao; Shengui Zhang; Yanping Xiao (Journal of Applied Mathematics)
The asymptotic equilibrium results for fuzzy differential systems GCP x′=f1t,x,y,y′=f2(t,x,y) are investigated, where f1t,x,y satisfies the compactness-type and f2t,x,y satisfies the dissipative-type conditions. It is worth mentioning that the uniformly continuous conditions of ft,x,y are removed in Song et al. (2005). That is to say, the results of Song et al. (2005) are extended. In addition, the global existence and asymptotic equilibrium results of fuzzy differential systems CP x′t=ft,x, x0=x0 are obtained.